2013
DOI: 10.1007/s00431-013-2224-z
|View full text |Cite
|
Sign up to set email alerts
|

Reference values of perfusion indices in hemodynamically stable newborns during the early neonatal period

Abstract: We aimed to determine reference values of perfusion index (PI) in healthy newborns during the early neonatal period. Preductal (right hand) and postductal (foot) PI values were assessed during the first 5 days of life by using a new generation pulse oximetry. A total of 241 newborn infants (196 [81.3 %] term and 45 [18.7 %] preterm) were enrolled to the study. On the first day, in term infants, the median (interquartile range [IQR]) preductal and postductal PI were 1.35 (1.02-1.91) and 0.88 (0.62-1.22), respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 15 publications
5
18
1
2
Order By: Relevance
“…Hakan et al reported a median PI value of 0.88(0.6, 1.26) in a cohort of 45 preterm infants [14] and Vidal et al found a median PI of 0.70 (0.50, 1.05) in a similar number of preterm infants [15]. We describe slightly higher values in preterm infants immediately after birth, 1.3 (0.86, 1.68).…”
Section: Discussionsupporting
confidence: 34%
See 1 more Smart Citation
“…Hakan et al reported a median PI value of 0.88(0.6, 1.26) in a cohort of 45 preterm infants [14] and Vidal et al found a median PI of 0.70 (0.50, 1.05) in a similar number of preterm infants [15]. We describe slightly higher values in preterm infants immediately after birth, 1.3 (0.86, 1.68).…”
Section: Discussionsupporting
confidence: 34%
“…It has also been shown that PI is highly reproducible in preterm infants [12], that this value increases over the first 3 days of life [10,13], and that PI may stabilise within 5 days of life [14]. Normative PI values have been described for preterm infants in the first day of life [14,15].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 94%
“…El abanico de situaciones clínicas en las que el IP ha demostrado su utilidad incluye la monitorización de la efectividad de la anestesia epidural, ya que un aumento del IP tras la administración de anestesia indica un incremento en la vasodilatación periférica, que normalmente se produce antes de la aparición del efecto anestésico (15) . En neonatos en estado crítico está contrastado que un bajo IP es una medida objetiva y precisa de enfermedad aguda (16) . De igual modo, este parámetro está siendo empleado para la estimación de la administración de volumen en pacientes con trauma grave, en estados de sepsis (17)(18)(19) , o en cirugías de reimplante y después de bypass cardiopulmonar, para la evaluación de la perfusión periférica.…”
Section: Discussionunclassified
“…12 Hakan et al aimed to determine reference values of perfusion index (PI) in healthy newborns during the early neonatal period. 26 Preductal (right hand) and postductal (foot) PI values were assessed during the first 5 days of life by using a new generation pulse oximeter and on the first day, in term infants, the median (interquartile range [IQR]) preductal and postductal PI values were 1.35 (1.02e1.91) and 0.88 (0.62e1.22), respectively. The sensitivity of our results is lower than those of Granelli et al, and at this point, it seems more logical to accept a PPI level of 0.70 as a cut-off.…”
Section: Scre E N-negaɵvementioning
confidence: 99%